Pelatihan Penggunaan Aplikasi Berbasis Learning Management Sysstem pada SMK Permata Kemiri Tangerang - winanti, winanti; Himmy'azz, Istajib Kulla Kulla; Kumoro, Dwi Ferdi Cahya; Kamar, Karnawi; Fernando, erick; Yulia, Yayah; Nurasiah, Nurasiah; Suwita, Jaka (IAHN Gde Pudja Mataram, 2024)
The training was conducted at Permata Kemiri Vocational School for one full day. During the Covid-29 pandemic, teachers experienced difficulties in delivering material considering that not all teachers understood technology such as using LMS. The resource person conveyed in detail and in detail regarding the LMS and the training was conducted for teachers by bringing their respective laptop facilities so that it was more optimal. During the training there was interaction between the resource person and the training participants so that the discussion ran smoothly. The aim of the training is to provide an understanding of the use of LMS for teachers as an interactive learning medium. The training activity was closed with a prayer and a group photo with the participants.